2008
DOI: 10.1111/j.1095-8649.2007.01702.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of genetic diversity at microsatellite loci and quantitative traits in hatchery populations of Japanese flounder Paralichthys olivaceus

Abstract: Relationships of genetic diversity at microsatellite loci and quantitative traits were examined in hatchery-produced populations of Japanese flounder using a relatively straightforward experiment. Five hatchery populations produced by wild-caught and domesticated broodstocks were used to examine the effects of different levels (one to three generations) of domestication on the genetic characteristics of hatchery populations. Allelic richness at seven microsatellite loci in all hatchery populations was lower th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 41 publications
0
10
1
Order By: Relevance
“…Our findings of higher genetic diversity in stocked lakes contrast with the usual perception that domestic fish should harbor lower genetic diversity (Hutchings & Fraser 2008; Shikano et al. 2008; Karaiskou et al.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our findings of higher genetic diversity in stocked lakes contrast with the usual perception that domestic fish should harbor lower genetic diversity (Hutchings & Fraser 2008; Shikano et al. 2008; Karaiskou et al.…”
Section: Discussioncontrasting
confidence: 99%
“…2008). As well, domestic fish are typically genetically distinct from wild populations, both in terms of allelic composition and genetic diversity (reviewed in Hutchings & Fraser 2008; Finnegan & Stevens 2008; Shikano et al. 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The lower allelic diversity of two of the hatchery populations compared with that of the wild populations may be associated with non‐random mating, small effective population sizes or both, although no historical genetic data are available. Several studies using molecular markers also have shown that cultured P. olivaceus tend to show reduced genetic variability compared with wild populations (Sekino et al , 2002; Liu et al , 2005; Kang et al , 2006; Shikano et al , 2008). The heterozygosity values of MS loci did not show pronounced differences between wild and hatchery populations, suggesting that allelic diversity is a more sensitive measure of genetic variation between wild and hatchery populations.…”
Section: Discussionmentioning
confidence: 99%
“…When the overall level of diversity of hatchery stocks was compared with that of the wild populations examined here, 94.1% of the allelic richness, on average, observed within the three wild samples was present in the hatchery samples, and the hatchery population displayed a slightly lower overall level of heterozygosity. Loss of genetic variation in hatchery strains, compared with wild populations, has been documented in several studies (Ryman and Ståhl, 1980;Liu et al, 2005;Shikano et al, 2008). The heterozygosity values of MS loci did not differ markedly between wild and hatchery populations, suggesting that allelic diversity is a more sensitive measure of genetic variation between wild and hatchery populations.…”
Section: Discussionmentioning
confidence: 88%